Qualitative analysis of the knowledge of applicants to transport engineering courses of study - Kliukas, Romualdas; Prentkovskis, Olegas; Daniūnas, Alfonsas (Transport, 2006)
The problems of selecting applicants to the Lithuanian universities and the level of knowledge of the applicants to transport engineering specialities will be discussed in this paper. A brief analysis of courses of studies in transport engineering at the Lithuanian univitersities is presented. Some statistical data reflecting the results of joint applicants admission to the Lithuanian higher schools are presented. The selection of applicants to study transport engineering courses at the Lithuanian universities is analyzed.First Published Online: 27 Oct 2010